Role of Twenty-Four-Hour Ambulatory Blood Pressure Monitoring in Children on Dialysis - Abanti Chaudhuri; Scott M. Sutherland; Brandy Begin; Kari Salsbery; Lonisa McCabe; Donald Potter; Steven R. Alexander; Cynthia J. Wong (2011)
Pre- or postdialysis BP recordings are imprecise, can be biased, and have poor test-retest reliability in children on dialysis. We aimed to examine the possible differences between pre- and postdialysis BP levels and 24-hour ambulatory BP monitoring (ABPM) in diagnosis of hypertension (HTN).Twenty-four children on dialysis had 24-hour ABPM in the interdialytic period, and values were compared with average pre- and postdialysis systolic BP (SBP) and diastolic BP (DBP) recordings that week. Each patient had an echocardiogram to determine presence of left ventricular hypertrophy (LVH).By ABPM, 8% of patients had white coat HTN and 12% had masked HTN. There was no significant difference in diagnosis of systolic HTN based on ABPM daytime SBP mean or load and postdialysis SBP. However, only 15% of patients had diastolic HTN based on postdialysis measures, whereas 46% of patients had significantly elevated daytime DBP loads and 71% had high nighttime DBP loads on ABPM. Forty-eight percent of patients were SBP nondippers. Children with LVH had higher daytime and nighttime SBP loads, significantly higher daytime and nighttime DBP loads, and lesser degree of nocturnal dipping of SBP compared with those who did not.ABPM is more informative than pre- and postdialysis BPs and improves the predictability of BP as a risk factor for target organ damage. Diagnosis and treatment monitoring of HTN among pediatric dialysis patients is enhanced with addition of ABPM.